Hatchery efficiency as a conservation tool in threatened sea turtle rookeries with high embryonic mortality. (15th October 2021) - Martins, Samir; Ferreira-Veiga, Nádia; Rodrigues, Zuleika; Querido, Adélcio; de Santos Loureiro, Nuno; Freire, Kátia; Abella, Elena; Oujo, Carolina; Marco, Adolfo
Abstract: Sea turtles are globally endangered and facing anthropogenic threats. To mitigate the negative impacts on sea turtle populations, different conservation strategies have been developed and implemented. For instance, when an endangered population suffers a high embryonic mortality from predation, human poaching, beach flooding or erosion, the relocation of clutches to safer and controlled areas can lower these threats. However, the use of hatcheries is controversially discussed, with some previous studies reporting negative results such as low hatching success, skewed sex ratio or phenotypic alterations of hatchlings. In this study, we evaluated the efficiency of beach hatcheries compared to in-situ incubation in Cabo Verde using data from six nesting seasons (2013–2018). During this study, several thousand high-risk clutches from loggerhead turtle ( Caretta caretta Linnaeus, 1758) were relocated to a hatchery constructed within the Sea Turtle Natural Reserve (STNR, Boa Vista Island). Our findings confirmed that the in-situ nests within the STNR have extremely high egg mortality that is usually over 70%. Mean hatching success of clutches relocated to hatcheries was significantly higher than in-situ clutches with mean values between 70 and 85%. No significant differences were observed in the incubation period, the size and the behavioural response of hatchlings between relocated and in-situ clutches. As long as a sea turtle population is endangered and hatching success is low, clutch relocation programs which are designed to have an impact at the population level, are considered an efficient tool that contributes to its recuperation. Nevertheless, strict recommendations that increase hatching success while maintaining natural hatchling phenotype must be implemented. Graphical abstract: Image 1 Highlights: This study evaluated the efficiency of beach hatcheries compared to in-situ incubation in Cabo Verde. Mean hatching success of clutches relocated to hatcheries was significantly higher than in-situ clutches. No differences were observed in the incubation period and morphology of hatchlings between relocated and in situ clutches.